A LOGICAL-METHODOLOGICAL ANALYSIS OF THE CONCEPT “AUTODECOMPOSITION OF SOCIAL SYSTEMS” - Мирошниченко, С. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the attempt of integrated determination of concept «social systems self-destruction» on the basis of semantically selected essence and content descriptions of concepts «self-destruction» and «social systems» is made.